Vapor-Phase Transport Deposition, Characterization, and Applications of Large Nanographenes - Abbas, Ahmad N.; Liu, Bilu; Narita, Akimitsu; Doessel, Lukas F.; Yang, Bo; Zhang, Wen; Tang, Jianshi; Wang, Kang L.; Raeder, Hans Joachim; Feng, Xinliang; Muellen, Klaus; Zhou, Chongwu (Journal of the American Chemical Society, 2015)
Recently, chemical synthesis of a range of large nanographene molecules with various shapes and sizes opened a new path to utilize them in various applications and devices. However, due to their extended aromatic cores and high molecular weight, film formation of large nanographene molecules, bearing more than 90 sp2 carbon atoms in aromatic cores, is very challenging, which has prevented their applications such as in thin-film transistors. Here, we developed an effective approach to prepare films of such large nanographene molecules using a vapor-phase transport (VPT) technique based on molecule sublimation. The VPT of these molecules was made possible by combining the molecules and the target substrate in a small confinement of vacuum-sealed glass tube, so that a small amount of sublimation can be utilized to create films. Surprisingly, such heavy and large molecules can be deposited on any substrate by this method to create films of assembled large nanographene molecules while maintaining their aromatic cores intact, which was confirmed using mass spectrometry measurements. Moreover, field-effect transistors based on these films are depleted and show significantly improved current on/off ratio compared to previous large nanographene-based transistors fabricated using liquid-phase-based process. Our work shows that VPT deposition can be a viable technique to prepare films based on large nanographene molecules and potentially other high molecular weight compounds, which may find exciting applications in electronics and optoelectronics. (Graph Presented).
CRIS-Team Scopus Importer:2023-03-20